Transfer of metallic nanostructures from solid-state substrates. Issue 48 (28th April 2016) - Kolářová, K.; Krajcar, R.; Ulbrich, P.; Švorčík, V.
Abstract : A novel technique for transferring dimensionally diverse metallic nanostructures from different kinds of substrates into chitosan foil is described. Abstract : A novel technique for transferring dimensionally diverse metallic nanostructures from different kinds of substrates into chitosan foil is described. We were able to obtain nanoparticles of different sizes and shapes incorporated into the surface of a biocompatible polymer with no restrictions on the process used to manufacture the structures supported on the initial substrate. We successfully transferred silver nanowires (NWs) from a nano-patterned polyethyleneterephthalate (PET) foil, and silver nanoparticles (NPs) from a microscope cover glass.